2023
DOI: 10.1038/s41598-023-31591-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-amylase, xylanase and cellulase on the rheological properties of bread dough enriched with oat bran

Abstract: A better understanding of dough rheology during processing is crucial in the bakery industry, since quality attributes of the final product are influenced by those properties. In this study, we investigated the effects of xylanase, α-amylase and cellulase on the rheological properties of bread dough enriched in oat bran. A DoughLAB was used to measure the mixing characteristics of dough. According to the results, adding a single enzyme did not significantly affect the water absorption, development time, or sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For a higher oat bran percentage, with the intention of improving the quality of bread incorporating 15% oat bran, individual and combined enzymes were used. In this study, to improve the rheological behavior of the dough during the breadmaking process, three enzymes were used: α-amylase, xylanase, and cellulase [73]. A similar study, carried out by Liu et al, stipulated that 15% oat bran be added to wheat flour dough, as the enzyme combination (α-amylase and xylanase) of oat bran can significantly improve the quality of Chinese steamed bread [74].…”
Section: Conventional Milling the Major Supplier Of Grain Losses Reus...mentioning
confidence: 99%
“…For a higher oat bran percentage, with the intention of improving the quality of bread incorporating 15% oat bran, individual and combined enzymes were used. In this study, to improve the rheological behavior of the dough during the breadmaking process, three enzymes were used: α-amylase, xylanase, and cellulase [73]. A similar study, carried out by Liu et al, stipulated that 15% oat bran be added to wheat flour dough, as the enzyme combination (α-amylase and xylanase) of oat bran can significantly improve the quality of Chinese steamed bread [74].…”
Section: Conventional Milling the Major Supplier Of Grain Losses Reus...mentioning
confidence: 99%
“…It decreased both softening and resistance to extension [17]. A study by Liu et al [18] demonstrated that by combining α-amylase, xylanase, and cellulase, a better rheological effect is obtained with the synergism.…”
Section: Introductionmentioning
confidence: 99%